HUBUNGAN BANTUAN OPERASIONAL SEKOLAH (BOS) DAN GURU PROFESIONAL TERHADAP NILAI UJIAN NASIONAL (UN) PADA SMP/MTS DI INDONESIA 2008-2012 - Siti Nurjanah (Fakultas Ekonomi Universitas Negeri Jakarta, 2014)
ABSTRACTThis research to aim the effect School Operational Fund and Profesianal Teacher on Score of National Examination.. This research use panel data with combine time series and cross section data, with secondary data that had published by Badan Pusat Statistik (BPS) and Ministry of Education and Culture. Estimation data with Eviews 7. This research use average score of National Examination on Junior High School educational level per provice in Indonesia, the number of school operational fund of education variable, and The number of teacher certification between provinces in indonesia year 2008-2012. The result is School Operational Fund have significant positive effect on Score of National Examination, Profesional Teacher have significant positive effect on Score of National Examination. The equation is Y = -23.27917+ 1.151364LnX1 + 0.216754LnX2. This equation means if variable School Operational Fund increase 1 percent will influence Score of National Examination increase for 1,151364, and if variable Profesional Teacher increase 1 percent will influence Score of National Examination increase for 0.216754. The R square value is 0.915965indicate that 91,59% Score of National Examination explained by both independent variable, those are School Operational Fund and profesioanl teacher. Key words: School Operational Fund, Profesional Teacher, Score of National Examination.